Mechanisms of Immune Activation by c9orf72-Expansions in Amyotrophic Lateral Sclerosis and Frontotemporal Dementia - Trageser, Kyle J.; Smith, Chad; Herman, Francis J.; Ono, Kenjiro; Pasinetti, Giulio Maria (Frontiers in Neuroscience, 2019)
Amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) are neurodegenerative disorders that often share neuromusculature, cognitive, behavioral, and personality deficits, with either a sporadic or genetic, familial etiology. In cases of familial ALS and FTD, G4C2 hexanucleotide repeat expansions (HRE) within chromosome 9 open reading frame 72 (C9orf72) are the predominant monogenic cause. ALS and FTD have been hypothesized to be a spectrum of disorders, with ALS manifesting primarily with neuromusculature defects and FTD with cognitive impairments. While the association of C9orf72 with disease onset and progression is well documented, the precise mechanisms through which this mutation elicits neurodegeneration have yet to be elucidated in their entirety. In vivo investigations have shown that the G4C2 sequences undergo repeat-associated non ATG dependent (RAN) translation which produces dipeptide repeat proteins of varying toxicities in both the sense and antisense direction. Of importance, arginine containing dipeptide repeat proteins have been shown to have the most deleterious effects on the cell, impairing nucleocytoplasmic transport, RNA metabolism, and oxidative stress pathways. Activation of inflammasomes in microglia and monocytes results in oxidative stress-mediated innate immune signaling and pro-inflammatory cytokine secretion which is reflected by the elevated levels of cytokines such as IL-1β and IL-18 as well as reactive oxygen species found in cases of ALS. Recent evidence suggests that microglial over reactivity contributes to the underlying mechanisms involved in the pathogenesis of C9orf72 mediated ALS / FTD via reciprocal relationships between the innate immune cells of the central nervous system and motor neurons. We suggest that G4C2 hexanucleotide repeat expansions mediate neuroinflammatory, genetic, and proteinopathic mechanisms that profoundly affect the pathogenesis of C9orf72 mediated ALS/FTD and furthermore that targeting the temporal relationship of innate immune cells and disease progression may yield novel treatment strategies.